The Development of Commercial Law: Perspectives from Chinese and European Traditions - Zhengyao, Wang; Narantuya, Lkhundev (Advances in Social Sciences Research Journal, 2026)
Our article argues that future reform of China’s commercial law should preserve its indigenous legal characteristics while selectively integrating advanced elements of foreign commercial law to enhance systemic coherence, adaptability, and market responsiveness. Commercial law, as a core branch of private law governing commercial transactions and market activities, has been shaped by diverse historical, cultural, and institutional traditions. Through a comparative analysis of the historical evolution of commercial law in Europe and China, the study highlights the distinct legal trajectories formed under Europe’s maritime civilization and decentralized city-state autonomy, and China’s agrarian civilization and centralized state structure. From the perspectives of legal culture and legal tradition, the article examines differences in conceptual foundations, normative structures, and regulatory principles between the two systems. The findings indicate that the effectiveness of European commercial law derives from its strong emphasis on the autonomy, efficiency, and specificity of commercial activities, whereas Chinese commercial law has historically been embedded within public-law-oriented governance and moral regulation. The study concludes by emphasizing the need for a balanced reform approach that combines institutional continuity with selective legal innovation.